CRIME INCIDENTS AND PREVENTION PRACTICES AMONG SELECTED MALLS IN NUEVA ECIJA - Mary Chris A. Austria; Irene M. Diaz, (INTERNATIONAL JOURNAL OF MODERN TRENDS IN SOCIAL SCIENCES (IJMTSS), 2024)
The objective of this study was to explore crime and crime prevention measures of business establishment in Cabanatuan, Nueva Ecija Philippines, Data were collected by means of respondents’ demographic profile, crime questionnaires as assessed by crime by crime against public moral, crimes against person, crime against property, and crime prevention questionnaire as evaluated by punitive prevention, environmental prevention, and mechanical prevention from mall owners (n=5) and their tenants (n=105). Employing a descriptive correlative design. Significant differences were found between owner and tenants responses in terms of crime (t=6.64, p>0.5) and crime prevention (t=4.29, p=0.05) significant negative relationship between crime and crime prevention (r = -0.56, p> 0.05) were also explored. Interview with professionals experienced law enforcers and retired high-ranking officials from the Philippine National Police (PNP) Region 3 and Philippine Army (7th Infantry Division) were conducted to support and validate findings. Crime prevention strategies that can serve to make commercial shopping malls safer and more secure were proposed